Who changes the course of history? Historical agency in the narratives of Spanish pre-service primary teachers. Issue 2 (17th October 2019) - Arias-Ferrer, Laura; Egea-Vivancos, Alejandro
Brief narratives created by pre-service teachers on a primary education degree course at the University of Murcia (Spain) were analysed to identify the ways in which they presented historical agents in European and Spanish history. The main units of analysis were categorized by the type of agent introduced in each narrative (individual, collective and institutional), then by identifying agents as either active or passive, and finally by describing the characteristics of their actions in terms of reasons and causes/consequences. The results reveal an emphasis on individual agents and the persistence of a superficial historical master narrative that perpetuates a distorted image of history.